Student-Oriented Islamic Religious Education Curriculum Design: Integrating Spiritual Values ​​and Modern Needs - Toni Gunawan Rambe (LECTURES: Journal of Islamic and Education Studies, 2025)
This study aims to develop an Islamic Religious Education (PAI) curriculum design that is oriented towards students' needs and potential. With a constructivist approach, this study examines how the PAI curriculum can be designed to increase student engagement in the learning process. Through an analysis of learning theories and best practices in education, this study suggests the implementation of a more flexible and contextual curriculum, which takes into account the differences in characteristics and needs of each student. The methods used are literature studies, observations, and interviews with PAI teachers and education practitioners. The results of the study indicate that a student-oriented curriculum design can increase students' learning motivation and understanding of PAI materials, as well as strengthen the application of Islamic values ​​in everyday life. The conclusion of this study is that an integrated PAI curriculum with a more personal and relevant approach to the student's context has great potential to increase the effectiveness of Islamic religious education in schools.